Foreign direct investments and relocations in business services – what are the locational factors? The case of Hungary - SASS, Magdolna (Cuadernos de Relaciones Laborales, 2010)
Hungary became host to various business services through relocations of these activities from other, higher cost locations, especially from Western Europe and through opening up new capacities. Locational advantages determine which countries are chosen as hosts to new or relocated service centres. For the case of Hungary, the analysis is carried out on the basis of eight detailed company case studies. The majority of these is vertical FDI (close to 100 % of export/sales ratio), and two companies represent a confluential case of vertical and horizontal (domestic market oriented) FDI, where sales to the domestic market are also important, though not dominating. The paper’s main aim is to make an attempt at contributing to filling some gaps in the literature, in terms of analysing locational advantages for vertical FDI in services, specifically in business services. It shows that locational advantages, taken into consideration by vertical and horizontal FDI differ from each other to a great extent. It identifies the various elements of locational advantages connected to the different elements of investment motives, in terms of cost reduction, reducing costs of disintegration of production, reducing other costs, and motives arising from the confluence of vertical and horizontal FDI, and the paper relates these elements to the specificities of the business services sector.